Analisis Pemanfaatan Media Pembelajaran Akuntansi Berbasis Adobe Flash Untuk Meningkatkan Hasil Belajar Siswa - Indah Wikiya Sari; Dian Novianti Sitompul (-)
The purpose of this study was to analyze the use of Adobe Flash based accounting learning media to improve student learning outcomes. The problems found that most students are more passive, reluctant, afraid or ashamed to express their opinions in accounting learning. In addition, there is less variation in teaching patterns using learning media.The research method uses the library research method by testing the validity of data in qualitative research including testing, credibility (internal validity), transferability (external validity), dependability (reliability), and confimability (objectivity). Based on the results of the analysis that adobe flash-based accounting learning media can increase and direct the attention of students so that it can lead to learning motivation, more direct interaction between students and their environment, and the possibility of students learning individually according to their abilities and interests